A prolonged pattern of the ionospheric depletion in the south of the 21 August 2017 solar eclipse path. (March 2020) - Guo, Ming; Xu, Na; Feng, Jian; Deng, Zhongxin
Abstract: During the American solar eclipse on 21 August 2017, the GNSS network was applied to record the ionospheric responses. Following the lunar shadow, the TEC depletion emerged over the eclipse path. After the eclipse end, the depletion in the north gradually disappeared and then the TEC enhancement emerged. The depletion in the south has continued for a long time. A sharp area between the enhancement and depletion regions appeared at 27°N latitude. Moreover, the depletion region were moving to south with larger and larger TEC decline after the eclipse maximum. The TEC over four selected places with same latitude and different eclipse obscurations is presented. Interestingly, the recovery periods of these TEC values are similar. The f o F2 and h m F2 in the enhancement and depletion regions displayed very different variation tendency. The eclipse-induced thermospheric winds are considered to further reduce the TEC after the eclipse. The formation of the sharp area in TEC may be related to the fountain effect. Highlights: The eclipse-induced depletion was moving to south with larger and larger TEC depletion after eclipse maximum. A sharp area between the enhancement and depletion regions appeared at the latitude of 27° N. The fountain effect and eclipse induced thermospheric winds may play an important role for the rare phenomena.